Embark on a Journey of Nutty Delights: Exploring the Future Harvests of Cashew Nuts in Tanzania's Southern Agricultural Zone - Yusuph, Ashura Rajab; Nyage, Asia Khamis; Jonas, Ajibu; Saleh, Husny Gibreel Musa (JIAN (Jurnal Ilmiah Administrasi Negara), 2024)
This study focused on time series forecasting of the yearly volume of cashew nut production in the Southern Agricultural Zone of Tanzania. This study aimed to predict the trend of cashew nut production in the Southern Agricultural Zone of Tanzania in metric tonnes and to forecast cashew nut production in the Southern Agricultural Zone of Tanzania from 2022 to 2026. The study adopted time series analytical methods. Annual secondary data of 32 years from 1989 to 2021 were collected from the Cashew nut Board of Tanzania, Data given were tested for stationarity before being modeled for forecasting. Time series analytical techniques particularly regression and Box-Jenkins (ARIMA) models were applied for modeling cashew nut production. Akaike's Information Criterion was applied in the ARIMA model selection. The study concluded that there was an increasing trend for cashew nut production if other factors remained constant. Also, the study concluded that ARIMA (0,1,1) was the best forecasting model for cashew nut production in the Southern Agricultural Zone of Tanzania. The value of the best Akaike Information Criterion (AIC) is 358.55. The study recommended that based on the expected increase of cashew nut production in the Southern Agricultural Zone of Tanzania, Tanzania needs to ensure that domestic markets and industries are protected to ensure equilibrium and any excess to be traded in foreign in the long run-in production of cash nut.